PENGARUH SIKAP KERJA, KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BAGIAN GIZI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI RSUD DR. ABDOER RAHEM SITUBONDO - Faiz Alzair Rizal Rahman; Riska Ayu Pramesthi; Lusiana Tulhusnah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study was to determine the influence of work attitude, leadership, and competence on the performance of nutrition department employees with work discipline as an intervening variable at Dr. Abdoer Rahem Regional General Hospital, Situbondo. The sample used in this study was a saturated sample of 32 permanent employees. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Squares (PLS-SEM). The results showed that work attitude had a significant positive effect on work discipline, leadership had a significant positive effect on work discipline, competence had a positive but insignificant effect on work discipline, work attitude had a significant negative effect on employee performance, leadership had a significant positive effect on employee performance, competence had a negative insignificant effect on work discipline, work discipline had a significant positive effect on employee performance, work attitude had a significant positive effect on employee performance through work discipline, leadership had a significant positive effect on employee performance, and competence had a significant negative effect on work discipline. Competence has a significant positive effect on employee performance through work discipline. Competence has a positive but insignificant effect on employee performance through work discipline.